Language learning styles and strategies - Жукова, Тетяна Василівна; Жукова, Татьяна Васильевна; Zhukova, Tetiana (My University, 2015)
We have often wondered why we have difficulties learning a foreign language from a particular instructor, whereas another seems to explain things in just the right way. There was a question why the course that somebody said was easy turned into a very complicated one for another person. The reason of these discrepancies may be differences in learning styles.
Keywords: learning style; visual learning; auditory learning; preferences; methods; learning strategies